Reading in dictatorship: military criticism - Noemi Voionmaa, Daniel (Árboles y Rizomas, 2023)
Censorship was an ideological cornerstone for the Chilean dictatorship (1973-1990). It was used routinely and impacted all aspects of life, in particular the cultural arena. Using archival documents (from the Ministries of Education and the Interior, as well as from the Secret Police, CNI), this essay attempts to investigate a specific phase of the censorship process: the rationale behind censoring. What were the arguments used to censor a text or a film? In other words, how did the cultural critique created by the dictatorship come into existence? I study in greater detail the analysis by the CNI of a book about torture in Chile published by Amnesty International as well as the ‘literary criticism’ of a poem written by a Colonel for the Directorate of Social Communication (DINACOS).